A contextual semi assisted project-based learning (SA-PjBL) about ocean wave energy: Creative thinking of pre-service physics teachers - Muhammad Satriawan; Liliasari Liliasari; Wawan Setiawan; Ade Gafar Abdullah; Rosmiati Rosmiati (Universitas PGRI Kanjuruhan Malang, 2021)
One of the factors that have become an obstacle in the development of techno-logy to use ocean wave energy as a renewable energy source is the lack of human resources who have expertise in this field. Therefore, in the long term, it is necessary to introduce basic knowledge to the young generation about wave energy and other renew-able energies and even must equip them with important skills such as creative thinking skills. This study aims to introduce students to how to utilize ocean waves as renewable energy while at the same time developing student creative thinking skills through semi-assisted project-based learning. This type of research is weak experiment research with one group pretest-posttest design research. The research was conducted on 31 pre-service physics physics teachers who were taking environmental physics lectures at a teacher training university in West Nusa Tenggara. The performance appraisal data were analyzed descriptively while the test result data were analyzed using the N-gain and the Wilcoxon test. Based on the results of data analysis, it was obtained <g> = 0.725, which means that there was a high increase in students' mastery of the concept of using ocean waves as a renewable energy source. In addition, the results of the performance appraisal data (score > 3) indicated that at each stage of learning, students were provided with indicators of creative thinking skills with very satisfied categories. Therefore, it can be concluded that environmental physics lectures using semi-assisted project-based learning able to improve students' mastery of concepts and creative thinking skills.